Review Essays. Issue 1 (1st July 2022) - Nielsen, Vibe; Lidchi, Henrietta; Mataga, Jesmael; Schroeder, Annelise; Isaac, Gwyneira; Rogerson, Riley
Abstract : How to Practice Decoloniality in Museums: Practicing Decoloniality in Museums: A Guide with Global Examples Csilla E. Ariese and Magdalena Wróblewska (Amsterdam: Amsterdam University Press, 2021) Listening to Art as the Voice of Our Time: The Online In-Conversation Series Indigenizing the (Art) Museum (Wapatah Centre for Indigenous Visual Knowledge/OCAD University, Toronto) National Museums in Africa: Some Reflections from the Continent: National Museums in Africa: Identity, History and Politics Edited by Raymond Silverman, George Abungu, and Peter Probst (London: Routledge 2022) From Paddock to Peace Garden: Heritage Politics and the Development of the Japanese Memorial Site at Featherston Shadows, Strings & Other Things : The Enchanting Theater of Puppets